IMPACT OF EXTENDED SOCIAL MEDIA TIME USAGE ON THE INTERPERSONAL SKILLS AMONG PSYCHOLOGY STUDENT AT BESTLINK COLLEGE OF THE PHILIPPINES (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2026)
This study aimed to identify the impact of extended social media usage on the interpersonal skills of Psychology students. Utilizing quantitative research in a descriptive manner, survey questionnaires were employed to gather data from a sample of Psychology students. The study focused on understanding how prolonged engagement with social media influences various aspects of interpersonal communication. This study involved administering self-made questionnaires, validated by psychometricians, to assess students' social media usage patterns and their perceived interpersonal skills. The survey focused on key areas such as active listening, empathy, teamwork, verbal communication, and non-verbal communication. The results show that the majority of respondents (69.70%) were aged 18-19. Female participants comprised 227 respondents, while male participants accounted for 103. Regarding social media accounts, 24.24% had four active accounts, 22.12% had three, 20.91% had two, 16.67% had one, and 16.06% had five or more. In terms of time spent on social media, 37.58% of respondents spent less than 8 hours, 31.82% spent exactly 8 hours, and 30.60% spent more than 8 hours daily. The composite mean results for interpersonal skills were as follows: active listening (3.20), empathy (3.20), teamwork (3.24), verbal communication (3.22), and non-verbal communication (3.22), with an overall weighted mean of 3.20. These results were interpreted as "Agree," indicating a general consensus among respondents on the influence of social media on their interpersonal skills. The findings suggest that social media has both positive and negative effects on interpersonal skills. While it provides opportunities for engagement and social interaction, digital communication also presents challenges that may impact face-to-face interactions. The results indicate that students recognize both the benefits and drawbacks of extended social media usage in relation to their interpersonal skills.
Keywords: interpersonal skills; social media; psychology students